Vulnerability to food insecurity among rural households in Sub-Saharan Africa - Adewale Olufunlola Yoade; Solomon Ayodeji Olatunji; Olabisi Omowumi Adeyemi (Agricultural and Resource Economics, 2018)
Purpose. The purpose of this study was to examine the factors that affect food shocks and how vulnerable are people to food shocks using Ife North Local Government Area of Osun State Nigeria as a case study. Methodology / approach. Data were collected from 150 households through multistage sampling from ten political wards in Ife North Local Government Area. Descriptive statistics was used to describe the socio-economic characteristics and profile food shocks experienced and identify the coping strategies employed among rural households in the study area. Results. The study revealed that majority of the household age range of between 40 to 59 (62.0 %), married (77.3 %). Also, majority of the respondent own their farm (85.3 %). The result shows that the shocks that are prevalent in the study area include high price of input (66.6 %), loss of close relatives (72.0 %), low agricultural production (64.6 %), pest and disease (66.6 %), hash economic time (54.0%), and Ill health (50%). The other shocks experienced having low prevalence among households are non-availability of labour (23.4 %), accident (32.0 %), flood (31.4%), and theft (35.4 %). Originality / scientific novelty. The age categorization of vulnerability to food insecurity indicates that household heads aged 80 and above are more vulnerable to food insecurity (0.7158) followed by those within age 21–39 (0.6895). Also, the distribution of household head by their educational level shows that the household that have no formal education (0.5123) are more vulnerable to food insecurity. Practical value / implications. The implication of this study is that Government should regulate price fluctuation of agricultural goods and inputs. The use of pesticides should be encouraged to prevent pests and disease prevalence. Also, agricultural credit should be made available to farmers.